Effect of estrogens on skin aging and the potential role of SERMs - Susan Stevenson (Dove Medical Press, 2007)
Susan Stevenson1, Julie Thornton21Burns & Plastic Surgery Research Unit, 2Cutaneous Research, Medical Biosciences, School of Life Sciences, University of Bradford, Bradford, UKAbstract: In humans, structural and functional changes attributable to aging are more visibly evident in the skin than in any other organ. Estrogens have significant effects on skin physiology and modulate epidermal keratinocytes, dermal fibroblasts and melanocytes, in addition to skin appendages including the hair follicle and the sebaceous gland. Importantly, skin aging can be significantly delayed by the administration of estrogen. This paper reviews the effects of estrogens on skin and the mechanisms by which estrogens can alleviate the changes due to aging that occur in human skin. The relevance of estrogen replacement therapy (HRT) in postmenopausal women and the potential value of selective estrogen receptor modulators (SERMs) as a therapy for diminishing skin aging are also highlighted.Keywords: estrogen receptors, skin, menopause, SERMs, HRT